When Innate Responses Matter: ILC2s Loom Large in Allergic Airway Inflammation - Vercelli, Donata (American journal of respiratory and critical care medicine, 2017)
At the end of September 2010, the world of asthma research was thrown into a turmoil by the results of a large genome-wide association study (GWAS) performed in 10,365 patients in Europe with physician-diagnosed asthma and 16,110 control subjects (1). [...]the mystery unraveled quite quickly, thanks to one of those experimental convergences that inspire awe in the biologists who witness them and become the subject of doctoral dissertations in history of science departments. Moro and colleagues reported innate production of Th2 cytokines by adipose tissue-associated lineage-negative lymphoid cells (4), Saenz and colleagues showed that IL-25 elicits a multipotent progenitor cell population that promotes Th2 cytokine responses in gut-associated lymphoid tissue (5), Neill and colleagues identified innate effector leukocytes that express IL13 and mediate type-2 immunity (6), and, last but not least, Price and colleagues traced these innate IL-13-expressing cells to essentially every mucosal site, including the lung (7). [...]unlike classical Th2 cells, ILC2s lack markers associated with classical cellular lineages, are rare in secondary lymphoid organs, exist mainly in nonlymphoid tissues as tissue-resident cells, and lack rearranged receptors for antigen responses (9, 10). The transcription factor RAR-related orphan receptor a plays a major role in the development of these cells (11), and the interaction of IL-2 with its receptor promotes their growth and regulates their function during lung inflammation (12)- hence, the inference that these newly discovered cells may be critical for asthma pathogenesis. In addition to cytokines, lipid mediators regulate human ILC2 function in patients with inflammatory conditions: by...